UJI TOKSISITAS EKSTRAK KULIT BATANG RENGAS (Gluta renghas) TERHADAP LARVA UDANG Artemia salina - Nursal "; Sri Wulandari; Budi Syahputra Rio (Biogenesis, 2016)
ABSTRACT This research was conducted on toxicity tests of rengas (Gluta renghas) bark extract to shrimp larvae Artemia salina in July to September 2015. This research aims to determine the toxicity of rengas (Gluta renghas) bark extract to shrimp larvae of Artemia salina. This research was carried out by experimental research using Brine Shrimp Lethality Test (BSLT) method which consisted of 5 treatments and 3 replications. Parameters measured were the mortality of shrimp larvae Artemia salina. The data obtained and analyzed by probit analysis using regression equation. The results showed that the extract of bark rengas (Gluta renghas) is toxic to shrimp larvae of Artemia salina. It can be seen from the LC50 values of 599.79 ppm. Key Words: Toxicity Test, Rengas (Gluta renghas), Artemia salina